Decline in oral function contributes to decreased activities of daily living at discharge in elderly patients with heart failure - Misaki Nakamura; Kanako Yamamoto; Shinichi Nozaki; Takahiro Saeki; Wataru Omi; Chieko Kato; Masaru Inoue; Tomoya Harada; Satoru Sakagami (PLoS ONE, 2025)
Low body weight is associated with decreased capacity for performing activities of daily living (ADLs) after discharge in patients with heart failure (HF). In particular, malnutrition and low body mass index (BMI) are considered poor prognostic factors. In this study, we aimed to examine the relationship between oral function and low body weight as well as the ability to perform ADLs in older patients with HF. To this end, we retrospectively examined patients with HF aged 75 years or older who had undergone oral function assessments. We examined various factors including age, sex, BMI, brain natriuretic peptide (BNP) levels, left ventricular ejection fraction (LVEF), Oral Health Assessment Tool-Japanese version (OHAT-J) scores, Barthel Index (BI) scores, and length of hospital stay. Patients were categorized into two groups based on their OHAT-J scores (OHAT-J ≤ 2 or OHAT-J ≥ 3), and their characteristics, including individual survey items, were compared. Additional correlation analyses were performed for BI at discharge. We found a negative correlation between the total OHAT-J score and BI at discharge. Specifically, lower BIs at discharge were observed in the group with poor scores for the items “lips,” “saliva,” and “dentures.” Oral dysfunction was associated with decreased ability to perform ADLs at discharge in older patients with HF. Thus, interdisciplinary interventions targeting oral health may improve the prognosis of patients with HF.